Theoretical melting profiles and denaturation maps of DNA with known sequence: fdDNA. - Vologodskii, A V (1978)
Differential melting profiles and denaturation maps are calculated for fdDNA whose sequence of nucleotides has been determined recently. The melting profiles for the total DNA and a number of its restriction fragments are compared with experimental data taken from literature. The comparison enables one to correlate a number of peaks on experimental melting profiles with the melting out of concrete regions of the nucleotide sequence. For three fragments very strong end effects are demonstrated on both theoretical and experimental profiles. These anomalous end effects are shown to be connected with a region highly enriched with AT-pairs. A possible influence of the heterogeneity of stacking interaction on the results obtained is discussed in detail.